Do 21-Gene Recurrence Score Influence Chemotherapy Decisions in T1bN0 Breast Cancer Patients? - Yu, Jing; Wu, Jiayi; Huang, Ou; He, Jianrong; Li, Zhu; Chen, Weiguo; Li, Yafen; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2020)
Purpose: Hormone receptor (HR)-positive breast cancer patients with tumor size <=1.0cm and negative node have favorable outcomes. The 21-gene Recurrence Score (RS) could predict response to chemotherapy for HR+ breast cancer, but its role in T1bN0 disease is challenging. Methods: T1bN0 breast cancer patients diagnosed between January 2014 and June 2019 with RS results were included and categorized as Low- (RS<18), Intermediate- (RS 18-30), or High-risk (RS>30) groups. Univariate and multivariate analysis were used to assess factors associated with RS distribution and chemotherapy recommendation. Chemotherapy decisions change and patient adherence after 21-gene RS testing were also evaluated. Results: Among 237 patients with T1bN0 tumors, proportions of Low-, Intermediate-, and High-risk RS were 19.8%, 63.3%, and 16.9%, respectively. Multivariate analysis found that ER expression (P = 0.011), PR expression (P <0.001), and Ki-67 index (P = 0.001) were independently associated with RS distribution. Adjuvant chemotherapy was recommended for 31.6% of patients, which was more frequently given to patients with higher tumor grade (Odds ratio (OR) = 2.99 for grade II, OR = 59.19 for grade III, P = 0.006), lymph vascular invasion (OR = 8.22, P = 0.032), Luminal-B subtype (OR = 5.68, P <0.001), and Intermediate-to High-risk RS (OR = 10.01 for Intermediate-risk, OR = 192.42 for High-risk, P <0.001). Chemotherapy decision change was found in 18.6% of patients, mainly in those with Intermediate- to High-risk RS tumor with the majority from no-chemotherapy to chemotherapy. The treatment compliance rate after the 21-gene RS testing with MDT was 95.4%. Conclusion: RS category was related to ER, PR, and Ki-67 expression, which was recognized as an independent factor of chemotherapy recommendation in T1bN0 breast cancer. The 21-gene RS testing would lead to a chemotherapy decision change rate of 18.6% as well as a high treatment adherence, which can be applied in T1bN0 patients.